2011
DOI: 10.1523/jneurosci.5463-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal and Ventral Parietal Contributions to Spatial Orienting in the Human Brain

Abstract: Influential functional magnetic resonance imaging (fMRI)-based models have involved a dorsal frontoparietal network in the orienting of both endogenous and exogenous attention, and a ventral system in attentional reorienting to task-relevant events. Nonetheless, given the low temporal resolution and susceptibility to epiphenomenal activations of fMRI, such depictions remain highly debated. We hereby benefited from the high temporal resolution and causal power of event-related transcranial magnetic stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 41 publications
13
95
0
Order By: Relevance
“…Neglect occurs more commonly and with greater severity after right than left hemisphere lesions in humans (Suchan and Karnath, 2011) and this asymmetry is consistent with the differential involvement of the right hemisphere in processes of attention and spatial representation, as revealed in many recent neuroimaging studies (Chica et al, 2011;Ptak and Schnider, 2011). Because of this hemispheric asymmetry, in this review, we will refer to neglect as 'left-sided' and to 'contralesional' as a lesion to the right hemisphere.…”
Section: The Term 'Hemispatial Neglect'supporting
confidence: 71%
“…Neglect occurs more commonly and with greater severity after right than left hemisphere lesions in humans (Suchan and Karnath, 2011) and this asymmetry is consistent with the differential involvement of the right hemisphere in processes of attention and spatial representation, as revealed in many recent neuroimaging studies (Chica et al, 2011;Ptak and Schnider, 2011). Because of this hemispheric asymmetry, in this review, we will refer to neglect as 'left-sided' and to 'contralesional' as a lesion to the right hemisphere.…”
Section: The Term 'Hemispatial Neglect'supporting
confidence: 71%
“…As to the functional attributes of the activation of IC 19 with increasing drug cue attentional bias, this network of brain areas comprises a ventral attention network involving the temporoparietal junction (TPJ), insula, and inferior frontal gyrus (Corbetta et al, 2008;Kucyi et al, 2012). This network is involved in the orienting of stimulus-driven attention (Chica et al, 2011) and the detection of salience for behaviorally relevant stimuli (Downar et al, 2002). The direct relationship of activity for this network and increasing cocaine attentional bias suggests that the varying attribution of salience and attention to cocaine stimuli resulted in individual variation in the cocaine attentional bias effect.…”
Section: Discussionmentioning
confidence: 99%
“…If these forms of attention depended on a single mechanism, the effects of endogenous and exogenous attention in the processing of stimuli should be qualitatively similar, differing only in quantitative aspects, such as the speed of the attentional movement or the duration of its effects (Müller & Rabbitt, 1989). However, recent research has clearly shown that endogenous and exogenous attention produce qualitatively different effects on the processing of information (Botta, Santangelo, Raffone, Lupiáñez, & Belardinelli, 2010;Funes, Lupiáñez, & Milliken, 2007;see Klein, 2004, for a review), can be deployed independently of each other (Berger, Henik, & Rafal, 2005;Chica, Lupiáñez, & Bartolomeo, 2006), and are implemented in partially distinct frontoparietal regions (Chica, Bartolomeo, & Valero-Cabré, 2011;Corbetta & Shulman, 2002). This accumulating evidence suggests that endogenous and exogenous attention consist of two separate attentional systems.…”
Section: Discussionmentioning
confidence: 99%